The Authoritative Text as Imperative to Comprehensibility of Legislation - Maxeiner, James R. (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
The most understandable of texts is of little use as law if it is not clear that it is authoritative. This is the comparative lesson of this essay. American law is—Americans say—indeterminate. American law is indeterminate because American texts, clear as they may be in wording, often are not authoritative; other texts apply too and may be inconsistent. German law is rarely indeterminate in this sense.This essay identifies in bullet-points some comparative aspects of clarity of American and German law. Why is American law indeterminate? Why is German law not? What, if anything, do these differences counsel for future European Union law? I identify five areas of differences. 1. Legal System and Statutes, 2. Lawmaking. 3. Federalism. 4. Constitutional Review and 5. Law Application.
Keywords: Rule of Law; Rechtsstaat; legal system; statutes; statutory precedent; lawmaking; federalism; constitutional review; legal certainty; legal indeterminacy